Consultation Liaison Psychiatry - Diagnostic concordance between referring physician and psychiatrist (Kerala Journal of Psychiatry, 2020)
Background: Consultation – liaison psychiatry (CLP) provides expert advice and act as a liaison. There is a high prevalence of psychiatric comorbidities among patients of other specialities, yet the referral rates are low, probably due to inadequate psychiatric awareness which can be assessed from the diagnostic concordance.Objective: To assess diagnostic concordance between the psychiatrist and referring doctor.Materials and Methods: This is a cross-sectional record-based study of all inpatients referred to CLP. Data was collected from CLP registry.Results: Most of the referrals were from General Medicine. The most common reason for referral was alcohol use disorders and common diagnoses made by referring physicians were alcohol use disorders, delirium and mood disorders, similar to the psychiatrist’s diagnoses; however, deliberate self harm (DSH), a common diagnosis made by the referring doctor, constituted only 4.2% of psychiatrist’s diagnoses. There was complete diagnostic concordance for 40.9%; perfect agreement was found for DSH and alcohol use disorders, substantial agreement for delirium and moderate agreement for mood disorders. The agreement was low for DSH with comorbid depression, other substance use disorders and organic mental disorders.Conclusion: The diagnostic concordance for common mental health problems is low, according to the present study. CLP needs to extend its educational function towards other specialities and it should be an active component of undergraduate psychiatric training.Keywords: Consultation Liaison Psychiatry, Diagnostic concordance
Keywords: consultation liaison; diagnostic concordance